An Overview of the University College Dublin Hollow Cylinder Apparatus - O'Kelly, Brendan (My University, 2001)
This presentation is divided into two sections. First, an example showing the influence of the principal stresses on the strength and deformation characteristics of a soil is discussed. Secondly, an overview of a unique HCA currently being commissioned in the Department of Civil Engineering, University College Dublin (UCD) is presented. The operating principles and the instrumentation used to load the sample and measure its deformational response are discussed.
Invited presentation at the 14th ISSMGE Young European Geotechnical Engineer?s Conference
PUBLISHED
Sofia, Bulgaria
Keywords: University College Dublin hollow cylinder apparatus